2018
DOI: 10.3390/s18092854
|View full text |Cite
|
Sign up to set email alerts
|

AFRP Influence on Parallel Bamboo Strand Lumber Beams

Abstract: The mechanical properties of parallel bamboo strand lumber beams could be improved by aramid fiber reinforced polymer (AFRP). So far, no investigation has been conducted on the strengthening of engineering bamboo beams using AFRP. In order to study the efficiency of AFRP reinforcement on parallel bamboo strand lumber beams, 13 beams had been tested and analyzed. Strain gauges and Laser Displacement Sensors were used for the tests. By sensing the strain and deformation data for the specimens under the applied l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In recent years, in order to alleviate the high demand for timber resources in China, the bamboo industry has developed rapidly. With natural bamboo as raw material, a series of new products, such as bamboo-woven plywood, bamboo mat plywood, parallel bamboo strand lumber (PBSL) [5][6][7][8][9], laminated bamboo lumber (LBL) [10][11][12][13][14] and Glubam [15] have been developed by using advanced composite and reconstituted technology and are gradually achieving a high level of industrialization.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in order to alleviate the high demand for timber resources in China, the bamboo industry has developed rapidly. With natural bamboo as raw material, a series of new products, such as bamboo-woven plywood, bamboo mat plywood, parallel bamboo strand lumber (PBSL) [5][6][7][8][9], laminated bamboo lumber (LBL) [10][11][12][13][14] and Glubam [15] have been developed by using advanced composite and reconstituted technology and are gradually achieving a high level of industrialization.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the failure of the strengthened beams started with tensile fractures on the bottom bamboo plates, and no slipping was observed between the strengthening materials and the original bamboo beams prior to the rupturing of the bamboo plates. Li et al [22,23] studied the efficiency of AFRP reinforcement on parallel bamboo strand lumber beams. The results showed that AFRP can effectively improve the flexural mechanical properties of parallel bamboo strand lumber beams.…”
Section: Introductionmentioning
confidence: 99%
“…Since PBSL is a new-type of composite material, relevant testing standards and criterion are not established. Previous research on PBSL as well as on laminated bamboo was primarily focused on flexural performance [14][15][16][17][18][19][20]. Limited research was reported on the experimental behaviour of PBSL under axial and eccentric compression as well as on analytical modelling of resulting stress-strain response [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%